Antimicrobial drug resistant non-typhoidal Salmonella enterica in commercial poultry value chain in Chitwan, Nepal - Amy Nelson; Sulochana Manandhar; Juliana Ruzante; Arrogya Gywali; Bimala Dhakal; Santosh Dulal; Rupendra Chaulagai; Sameer M. Dixit (BMC, 2020)
Abstract Background Antimicrobial resistance (AMR) among bacterial pathogens is a fast-growing public health concern. AMR in non-typhoidal Salmonella serovars (NTS) among food animals is of special concern as this may transmit resistant pathogens to humans during handling or consumption of animal products. In Nepal, the possibility of AMR Salmonella serovars among food animals is an important area of research, particularly in light of the rapidly growing poultry industry, lack of surveillance and proper biosecurity measures; and paucity of relevant data. This study was conducted with the aim to estimate the burden of NTS and associated antimicrobial resistance in the environments of commercial poultry farms and the poultry carcasses in slaughter house. This study also intends to find some basic knowledge of the poultry farmers and their practice relating to the use of antimicrobials, vaccination and biosecurity measures. Methods Taking one health approach, a cross-sectional study was carried out in Chitwan district of Nepal between May and October 2017. Various environmental samples viz. farm litter, feed, water, poultry faeces, vehicle swabs, farm swabs from 12 broiler poultry farms and various sections of poultry carcasses from 21 slaughter houses were aseptically collected. These were microbiologically assessed for the presence of NTS serovars and their phenotypic and genotypic indicators of antimicrobial resistance. The poultry farmers were also briefly interviewed regarding their basic biosecurity related knowledge and practices before collecting the environmental samples. Results Overall, of total environmental samples collected, 50% (31/62) tested positive for NTS serovars with environmental swabs (70%, 8/12) being the most culture positive sample types. Similarly, of 159 tissue samples collected from 24 carcasses, 79% (126/159) were culture positive for NTS serovars. Nearly 97% (153/157) of isolates showed antimicrobial resistance to tetracycline, while 11% (17/157) to ciprofloxacin and 5% (8/157) of isolates were resistant against azithromycin. All 157 isolates were sensitive to meropenem. In terms of AMR genes, tetA (83%, 131/157), QrnS (40%,64/157), mefA (8%, 13/157) and VIM-1 (0.6%, 1/157) were detected in the isolates that corresponded to the AMR to tetracycline, ciprofloxacin, azithromycin and meropenem respectively. In farmers interview, only 42% (5/12) of farmers mentioned of using basic biosecurity measures such as applying lime powder around the farm; 84% (10/12) of farmers reported vaccinating their birds with some vaccine and 75% (9/12) of farmers used various antimicrobials prophylactically such as neomycin (33%, 4/12), colistin (33%, 4/12), furaltadone (33%, 4/12), doxycycline (25%, 3/12), sulfatrimethoprim (25%, 3/12) and tylosin (16%, 2/12). Conclusions This study revealed gross contamination of farm environment and subsequent poultry meat samples with NTS serovars that were resistant to several clinically important antimicrobials. Further, inadequacy of even basic biosecurity measures and frequent prophylactic use of antimicrobials in the commercial poultry farms was observed. This reinforces an urgent need to raise awareness and implement proper biosecurity approaches from farms to slaughter houses in order to reduce the burden of NTS contamination of surrounding environment and poultry products. Further, high prevalence AMR among NTS isolates also underscores the need to strengthen the policies to prevent the rampant use of clinically used human antimicrobials in poultry sector.